Predictive value of the Diverticular Inflammation and Complication Assessment (DICA) endoscopic classification on the outcome of diverticular disease of the colon: An international study. Issue 4 (August 2016) - Tursi, Antonio; Brandimarte, Giovanni; Di Mario, Francesco; Annunziata, Maria L; Bafutto, Mauro; Bianco, Maria A; Colucci, Raffaele; Conigliaro, Rita; Danese, Silvio; De Bastiani, Rudi; Elisei, Walter; Escalante, Ricardo; et al.
Background: Diverticular Inflammation and Complication Assessment (DICA) endoscopic classification has been recently developed for patients suffering from diverticulosis and diverticular disease. Aims: We assessed retrospectively the predictive value of DICA in patients for whom endoscopic data and clinical follow-up were available. Methods: For each patient, we recorded: age, severity of DICA, presence of abdominal pain, C-reactive protein and faecal calprotectin test (if available) at the time of diagnosis; months of follow-up; therapy taken during the follow-up to maintain remission (if any); occurrence/recurrence of diverticulitis; need of surgery. Results: We enrolled 1651 patients (793 M, 858 F, mean age 66.6 ± 11.1 years): 939 (56.9%) patients were classified as DICA 1, 501 (30.3%) patients as DICA 2 and 211 (12.8%) patients as DICA 3. The median follow-up was 24 (9–38) months. Acute diverticulitis (AD) occurred/recurred in 263 (15.9%) patients; surgery was necessary in 57 (21.7%) cases. DICA was the only factor significantly associated to the occurrence/recurrence of diverticulitis and surgery either at univariate (χ 2  = 405.029; p  < 0.0001) or multivariate analysis (hazard ratio = 4.319, 95% confidence interval (CI) 3.639–5.126; p  < 0.0001). Only in DICA 2 patients was therapy effective for prevention of AD occurrence/recurrence with a hazard ratio (95% CI) of 0.598 (0.391–0.914) ( p  = 0.006, log rank test). Mesalazine-based therapies reduced the risk of AD occurrence/recurrence and needs of surgery with a hazard ratio (95% CI) of 0.2103 (0.122–0.364) and 0.459 (0.258–0.818), respectively. Conclusions: DICA classification is a valid parameter to predict the risk of diverticulitis occurrence/recurrence in patients suffering from diverticular disease of the colon.